Evaluation of apoptosis regulatory proteins in response to PUVA therapy for psoriasis. Issue 1 (2nd January 2013) - El‐Domyati, Moetaz; Moftah, Noha H.; Nasif, Ghada A.; Abdel‐Wahab, Hossam M.; Barakat, Manal T.; Abdel‐Aziz, Rasha T.
Summary Background The histopathologic changes characteristic of psoriasis might be related to suppressed apoptosis. One of the actions of psoralen ultraviolet A (PUVA) in psoriasis could be exerted through induction of apoptosis of keratinocytes and lymphocytes; however, its exact molecular mechanism is still confusing. Aim In this study, we evaluated the expression of pro‐apoptotic (P53, Fas and Bax) and anti‐apoptotic (Bcl‐2) proteins correlating it with apoptotic index (AI) and epidermal thickness in psoriatic skin before and after PUVA therapy. Methods Lesional and non‐lesional skin biopsy specimens were obtained from 10 patients with generalized plaque psoriasis before and after 8 weeks of PUVA therapy. Histometric measurements of epidermal thickness as well as P53, Fas, Bax and Bcl‐2 expressions were evaluated using immunoperoxidase technique and apoptotic cells were detected by terminal deoxynucleotide transferase (TdT) mediated deoxyuridine triphosphate nick end labeling (TUNEL) method. Results After PUVA therapy, the epidermal thickness of psoriatic skin was significantly decreased (P < 0.001) and keratinocytes of psoriatic skin showed significant increased expression of P53 (P < 0.001), Fas (P < 0.001) and Bcl‐2 (P < 0.001) with no significant change in Bax expression (P > 0.05). Apart from significant decrease of Bcl‐2 expression (P = 0.01), no significant difference in all previous markers were encountered in lymphocytes (P53, Fas and Bax; P > 0.05) after PUVA therapy. The AI was significantly increased (P = 0.008) after PUVA therapy especially in lymphocytes (P = 0.002). Conclusion The present study suggests that one of the actions of PUVA therapy in psoriasis might be exerted through induction of apoptosis especially of lymphocytes by suppression of Bcl‐2 expression and of keratinocytes through P53 and Fas pathways leading to healing of psoriasis.